Writing differently. Issue 1 (February 2019) - Gilmore, Sarah; Harding, Nancy; Helin, Jenny; Pullen, Alison
This special issue of Management Learning on 'Writing Differently' builds on a groundswell of resistance to 'scientific' norms of academic writing. These norms are restrictive, inhibit the development of knowledge and excise much of what it is to be human from our learning, teaching and research. Contributors to the special issue explore how, released from these restrictions, it is possible to touch vulnerable flesh and invoke new political and ethical practices. Through changing our norms of writing, we explore different modes of learning and change how and what we teach. By bringing the previously excised vast hinterlands of life and lives to the fore, we create the intellectual space to engender new ideas as well as more collaborative forms of learning. In so doing, we foster alternative conversations as to how we might constitute new, highly ethical and humanitarian organisations.